Thermal degradation of the anthocyanins extracts from jabuticaba peels and red cabbage leaves - Souza, Priscila Pereira; Robazza, Weber Silva; Galvão, Alessandro Cazonatto (Scientia Plena, 2020)
Anthocyanins are phenolic compounds with tinctorial capacity. Their successful extraction and purification depends on information associated with their thermal stability. This work presents a study on the degradation kinetics of the anthocyanins in the peels of the jabuticaba fruits and the leaves of red cabbage through assays performed at different temperatures (ranging from 323.15 K to 363.15 K) and degradation times (up to 10 hours for jabuticaba and 30 hours for red cabbage). Total monomeric anthocyanins were determined through the pH differential method. Regarding the extraction, it was observed a larger quantity of anthocyanins from red cabbage extracts, with an average value of 1.3774 mg‧gdb-1, when compared to jabuticaba extracts, with an average value of 1.0479 mg‧gdb-1. The results suggest that the anthocyanins in the red cabbage leaves are much more thermally stable than the anthocyanins in the jabuticaba peels. The experimental assays suggest that the thermal degradation reaction proceeds according to a first-order kinetics model for the anthocyanins in both sources under study. The experimental values were treated according to their thermodynamic relations, which indicated that the thermal degradation process of the evaluated anthocyanins is endothermic and not spontaneous, with similar values of 64.8 kJ‧mol-1 for the red cabbage and 70.2 kJ‧mol-1 for the jabuticaba.